A framework for diversifying the artificial intelligence talent pipeline: Collaboration between historically Black colleges and universities, industry, and government - Liu, Larry; Ali, Amjad; Ojeme, Blessing (American Journal of STEM Education, 2025)
The rise of Artificial Intelligence (AI) creates significant opportunities for economies and societies but its development is hampered by insufficient availability of diverse talent from traditionally disadvantaged communities including African Americans. We build on the concept of the talent pipeline, a pool of qualified candidates ready to fill organizational vacancies, to propose a framework for how to diversify the AI workforce. We argue that there needs to be a synergy between Historically Black Colleges and Universities (HBCUs), industry and government in order to create a diverse and inclusive workforce in AI. We point to actionable recommendations for organizations and successful existing examples for such talent pipelines on which we can build.